Bioactive compounds of endophytic fungi isolated from Mammea siamensis, Mesua ferrea, AND Calophyllum inophyllum - Paulwatt Nuclear (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2010